EFEKTIVITAS STERILISASI KIMIA DENGAN LARUTAN DAUN SUKUN PADA ALAT KEDOKTERAN GIGI - Irma Haida Yuliana Siregar; Endah Aryati Ekoningtyas (Jurnal Kesehatan Gigi, 2017)
TITLETHE EFFECTIVENESS OF CHEMICAL STERILIZATION  WITH A BREADFRUIT LEAF SOLUTION TO DENTAL EQUIPMENTSABSTRACTChemical sterilization refers to a technique of sterilization making use of a chemical agent. One of the chemical agent using for it is chlorine. On the other hand, Sukun’s leaves conceive flavonoid which has the effect of anti bacteri and antioxidant. This study aimed to know the effectivity of using Sukun’s leaves solution for sterilizing dental equipments.The type of this study was true experimental research with control group. There were two interventions wih three times repetition per each. The samples were excavator contaminated with bacteri form gangraen teeth. The bacteri were swabed before and afdter intervention. The sukun’s leaves solution used in 20%, 40% and 60% concentration. The bacteri were incubated 1 x 24 hours and then counted with colony counter to see the effectivity of the solution. The data were analyzed descriptively and statistically.The result showed that sukun’s leaves solution had the signifficant effet to decrease the bacteri at 60% concentration. It has equal effect with chlorin 0,5% Keywords : sukun’s leaves solution, chemical sterilization, dental equipments